2016
DOI: 10.1080/1067828x.2016.1175983
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Male Conduct-Disordered Patients in Substance Use Disorder Treatment: Examining the “Limited Prosocial Emotions” Specifier

Abstract: To our knowledge, this is the first study to examine the DSM-5-defined conduct disorder (CD) with limited prosocial emotions (LPE) among adolescents in substance use disorder (SUD) treatment, despite the high rates of CD in this population. We tested previously published methods of LPE categorization in a sample of male conduct-disordered patients in SUD treatment (n=196). CD with LPE patients did not demonstrate a distinct pattern in terms of demographics or co-morbidity regardless of the categorization metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Conduct-problem adolescents without LPE, compared to those with LPE, had significantly lower ICU total scores ( p <0.001) and were about 0.6 years older than those with LPE ( p =0.04). In agreement with our predictions and prior work (Sakai et al, 2016b), these two patient groups were similar in their diagnostic profiles and did not significantly differ in cannabis, tobacco, alcohol or cocaine use disorder, conduct disorder diagnosis, whole-life major depression prevalence, or ADHD symptom severity.…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…Conduct-problem adolescents without LPE, compared to those with LPE, had significantly lower ICU total scores ( p <0.001) and were about 0.6 years older than those with LPE ( p =0.04). In agreement with our predictions and prior work (Sakai et al, 2016b), these two patient groups were similar in their diagnostic profiles and did not significantly differ in cannabis, tobacco, alcohol or cocaine use disorder, conduct disorder diagnosis, whole-life major depression prevalence, or ADHD symptom severity.…”
Section: Methodssupporting
confidence: 92%
“…An alternate strategy is to utilize other conduct-problem youths (i.e., with serious antisocial behavior problems but scoring at about average levels for callous-unemotional traits) as a control (Hwang et al, 2016). We have previously demonstrated that patients with conduct disorder with and without LPE have similar patterns of co-morbidity in terms of prevalence of depression, ADHD, and specific substance use disorders when recruited in the same manner as done in this study (Sakai et al, 2016b). A small set of work in detained adolescents has shown similar results (Colins and Vermeiren, 2013; Van Damme et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Several studies show that boys with CD and meeting criteria for the LPE specifier present more severe antisocial behavior and decreased prosocial behavior (McMahon et al, 2010;Kahn et al, 2012;Pardini et al, 2012;Colins and Andershed, 2015;Kimonis et al, 2015;Pechorro et al, 2015), with similar findings for girls (Pardini et al, 2012;Colins and Andershed, 2015). However, recent studies find limited usefulness of the cut-off score for the criteria of the LPE specifier in detained youths (Colins and Vermeiren, 2013;Colins, 2016;Colins et al, 2017), in former refugees (Latzman et al, 2016), and in conduct-disordered youths with substance abuse (Sakai et al, 2016). Only 4.5-7% of the variance in aggression was explained by the LPE specifier (Jambroes et al, 2016).…”
Section: Introductionmentioning
confidence: 96%